(untitled) - Sevcikova, Veronika (Aura musica, 2021)
The contribution is concerned with the reflexion of the personality and work of Ennio Morricone in music students (Department of Music of the Faculty of Education of the University of Ostrava). By means of a partial four-tier qualitative research using three methods of ascertaining, the contribution identifies the place of Ennio Morricone and his film music in the knowledge and attitudes of the present university students of music. The study commemorates Ennio Morricone's death in July (6 July 2020).
Keywords: Ennio Morricone; university students of music; four-tier qualitative research; interest preferences questionnaire; film music knowledge test; listening test - visualisation; functional use of film music and scaling